Perancangan Sistem Informasi Manajemen Proyek untuk Pengelolaan Arsip Ijazah - Wulan Indah Lestari; Yahfizham (CV. ITTC INDONESIA, 2024)
In the digital age, education data management is crucial. This article highlights the need for a modern and integrated diploma archiving system to improve efficiency, security and accessibility of information. Many educational institutions still use outdated archiving systems. The risk of data corruption or loss, inaccuracies and data duplication are also problems that arise due to outdated archiving systems. The research methodology uses UML for design. The software development method uses the waterfall approach. The results of this study include a needs analysis, usecase diagram, and system flowchart that produce a website-based document archive system.